Klasifikasi Status Gunung Berapi dengan Metode Learning Vector Quantization (LVQ) - Chelsa Farah Virkhansa; Budi Darma Setiawan; Candra Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
There are 129 active volcanoes and 500 inactive volcanoes located in Indonesia. Residents who live around areas that are susceptible to volcanic eruptions are quite numerous, which is as much as 10% of Indonesia's population. From the number of volcanoes that are still active there are only 69 mountains monitored, so there are still many active volcanoes which are not well monitored, which is around 40%. So that information on the status of the volcano is needed as quickly and accurately as possible to reduce the impact caused by the volcanic eruption. In this research, volcanic status classification will be carried out using the Learning Vector Quantization method. this study uses data totaling 110 data. The data was obtained from the website of the Volcanology Center and Geological Disaster Mitigation (PVMBG). From the tests that have been done, the highest accuracy is 88% when using the learning rate 0.1, the learning rate deduction is 0.1 and the minimum learning rate is 0.01.